The Philosophy of Living With Fungi - Sukardi Hastiono (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2004)
The philosophy of living with fungi is explained in this paper. An undeniable fact is that God creates living creatures in this world with purposes. Every creature, including fungus, has its own use and purpose. The presence of fungi, comprising mushrooms, moulds and yeast in human lives, including their advantages and disadvantages, makes human provided with intellect and thought by The Creator, observe, examine and dissect the fungus life as far as it can be done limited by the intellect and thought given. On fungi with advantages, human beings make effort to examine the behavior and characteristics so the creatures can be as far as possible used for human benefit and welfare.. Likewise, against fungi that have potency to cause disadvantages, for instance diseases, (mycoses, mycotoxicosis and fungus allergy) in human beings, animals, and plants, researches are directed to efforts in healing the diseases caused by the fungi, for example drugs for anti-fungus or similar kinds. In the later case, biological control by using other creatures with antagonistic characters has also been done by human beings. Using various more sophisticated technologies, human beings have future prospect in handling the fungi. The philosophy obtained from living with fungi is that in facing benefited fungi, human beings make effort to maximally utilize them, while in facing disadvantaged fungi, human beings seek solutions the disadvantages obtained can be eliminated or minimised as much as possible . Key words: Fungi, mushrooms, moulds, yeast, advantage, disadvantage, disease disturbance